Uso da água cinza no crescimento inicial do mamoeiro e maracujazeiro em áreas de produção familiar - Oliveira, Herison Alves de (Universidade Federal Rural do Semi-Árido, 2019)
Agriculture is one of the main sources of income for settlements and rural communities in the state of Rio Grande do Norte, where the use of water is extremely necessary to enable the production of vegetables and fruits. The scarcity of water resources brings dozens of damage to the population, making livestock unviable, harming water supply and hindering agricultural production, especially small farmers. The water reuse is an alternative to minimize the problem of drought that, in addition to meeting the water demand of the plant, also provides nutrients necessary for its development. The objective of this work was to evaluate the use of treated gray water on the growth and nutrient content of papaya and passion fruit seedlings The experiment was carried out in the Jurema rural settlement, located in the municipality of Mossoró-RN. For each crop, the non-destructive analyzes were performed: height, stem diameter and number of leaves, being the experimental arrangement in plots sub-divided in time, arranged in the plot three types of irrigation water: T - Treated gray water; A - supply water and M - 1: 1 effluent and water supply mixture for each crop. In the subplot, the evaluation times 30, 60 and 75 days after sowing were distributed with three blocks and five plants per block. For each crop, the destructive analyzes were also carried out: root length, dry mass and nutrient content, with a simple randomized block design with three treatments, corresponding to the irrigation water (T, A and M), with three blocks and five plants per block. The irrigation with treated gray water improved the production of papaya and passion fruit, promoting higher growth and biomass accumulation in relation to water supply. For papaya, nitrogen, potassium, calcium, magnesium, iron, manganese and zinc contents in the plant tissue were not altered by irrigation with gray water, whereas for passion fruit, nitrogen, iron and zinc contents were increased by irrigation with treated gray water
Keywords: Carica papaya L.; Passiflora edulis L.; Reúso de água; Efluente; Carica papaya L.; Passiflora edulis L.; Water reuse; Effluent; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO